Stress-Induced Visceral Pain: Toward Animal Models of Irritable-Bowel Syndrome and Associated Comorbidities - Moloney, Rachel D.; O’Mahony, Siobhain M.; Dinan, Timothy G.; Cryan, John F. (Frontiers in Psychiatry, 2015)
Visceral pain is a global term used to describe pain originating from the internal organs, which is distinct from somatic pain. It is a hallmark of functional gastrointestinal disorders such as irritable bowel syndrome (IBS). Currently the treatment strategies targeting visceral pain are unsatisfactory, with development of novel therapeutics hindered by a lack of detailed knowledge of the underlying mechanisms. Stress has long been implicated in the pathophysiology of visceral pain in both preclinical and clinical studies. Here we discuss the complex aetiology of visceral pain reviewing our current understanding in the context of the role of stress, gender, gut microbiota alterations, and immune functioning. Furthermore we review the role of glutamate, GABA, and epigenetic mechanisms as possible therapeutic strategies for the treatment of visceral pain for which there is an unmet medical need. Moreover we discuss the most widely described rodent models used to model visceral pain in the preclinical setting. The theory behind, and application of, animal models is key for both the understanding of underlying mechanisms and design of future therapeutic interventions. Taken together, it is apparent that stress-induced visceral pain and it’s psychiatric co-morbidities, as typified by IBS, has a multifaceted aetiology. Moreover, treatment strategies still lag far behind when compared to other pain modalities. The development of novel, effective and specific therapeutics for the treatment of visceral pain has never been more pertinent.